Individual and environmental parameters in children with and without developmental coordination disorder: associations with physical activity and body mass index - Valentini, Nadia Cristina; Souza, Priscila Silva de; Souza, Mariele Santayana de; Nobre, Glauber Carvalho (Frontiers in Pediatrics, 2023)
Physical Activity (PA) is a complex behavior, and the relevance of other factors such as BMI, SES and children's behavior at school and home still lacks investigation for children, especially those at risk or with Developmental Coordination Disorder (DCD). The objective of this study was to examine whether socioeconomic status (SES), school’s spaces for children's movement, active play, screen time, motor skill proficiency, perceived motor competence, and engagement in the physical education lessons were associated with PA and BMI in children with typical development (TD), at risk of DCD (r-DCD), and with DCD. Children (N= 352; 4–10-year-old) from six public schools in a major urban city, in southern of Brazil, were assessed regarding motor skill proficiency (locomotor and ball skills), perceived motor competence, and weight status. PA and engagement in the lesson were assessed using pedometers and a behavior checklist of motor experience of success. Parents recorded the daily time that children spent on screen and in active play. The hierarchical multivariate linear regressions showed that age, sex, SES, Schools with more favorable space for children's movement, locomotor and ball skills, and successful engagement, were associated with PA for children with TD. Age, screen time, locomotor, and successful engagement were associated with BMI. For children at r-DCD, age, sex, SES, with more favorable space for children's movement, and locomotor were associated with PA. Age, active play and screen time were associated with BMI. For children with DCD, sex, SES, Schools with more favorable space for children's movement, screen time, and successful engagement were associated with PA. Age, sex, active play, and screen time were associated with BMI. Different factors were associated with PA and BMI for children with different levels of motor impairment (r-DCD and DCD) and children with TD.